A META ETHNOGRAPHIC ANALYSIS OF STATUS OF TRIBAL WIDOW REMARRIAGE AND IMMOVABLE PROPERTY RELATION - Kumari, Deepa; Sen Chaudhuri, Sucheta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Jharkhand government’s declaration to the widow remarriage incentive scheme 2024 (Ranjan 2024) is an eye opener to rethink in the matter of right of tribal widow’s remarriage. Because, many tribal communities, widow remarriage receives positive sanction as a custom in practice. The central argument of this research paper is that in which kind of situation tribal widows require incentive for remarriage when communities have positive sanction to widow remarriage. To understand the nature of the problem it aims at comparative study to see patterns of widow remarriages in different tribal cultural practices. Most of the communities are referred in the discussion are from North East India and Central India. Reason behind selecting these communities is that they are predominantly tribal state under 6th schedule and from Central India states have 5th schedule provision. To understand economic vulnerability of widows the parameter- “the nature of land inheritance” in their respective communities is taken into data analysis.